Patent litigation in Europe: Can start-ups and growth companies defend their rights? - Rantasaari, Krista (fi=Turun yliopisto|en=University of Turku|, 2021)
The patent regime should provide adequate measures when start-ups and growth companies are accused of or receive threats for infringing patent holder’s rights. Fighting against infringements is a financial burden that eventually hinders a com¬pany’s growth. This is more damaging to smaller companies. Patents can also be asserted inappropriately; such assertions infringe on the functions of patents, and deliberately go beyond the claims and boundaries of what is protected. The research established three preliminary aspects for discussion. First, start-ups and growth companies have a central role in innovations activities. Second, the European patent enforcement scene has to address both the cross-border exploita¬tion of patents and the unitary patent system regime that is coming into force. Third, start-ups and growth companies must be able to retaliate against infringements with adequate measures. Patents are seen as an important economic tool with potentially significant com¬mercial value. As a corollary, their use has broadened and diversified. Thus, patent related transactions have increased and new structures and ways of monetizing pat¬ents have emerged as patent funds. Patent funds bring opportunities as they are able to monetize patents and to finance companies; however, they also cause difficulties and litigation is used as a threat to obtain financial compensation. In addition, patent laws and their applications are challenged by the growing interdependence of various entities in different countries. The question addressed throughout the whole research is: How can efficiency and legal certainty be increased through patent enforcement regulations so that the European patent enforcement regime supports start-ups and growth companies? Legal certainty and efficiency have been determined as the normative goals for this research and the perspective applied is that of the New Institutional Economics (NIE) and comparative law. NIE studies how institutions interact with organisations where both are interactive by nature. The legal institutions recognised are the relevant rules and case law and the organizations are entities such as companies and patent funds. The institutional environment establishes the general framework in which the insti¬tutional arrangements occur. This dissertation examines procedural safeguards such as fee shifting, preliminary injunctions and bifurcation. It also investigates the multiple defendants’ rule. Furthermore, the abuse of rights principle, the abuse of dominant position, the IP Enforcement Directive and unjustified threats are examined. In this research, the relevant legal institutions are the European Union law and the legislation of selected European countries. The focus is mainly on Germany, the United Kingdom and the Netherlands as these countries deal with the majority of European patent cases. The measures studied in this dissertation provide tools for start-ups and growth companies when defending their rights. As regards certain of these tools, coherence in the judicial interpretation has been achieved. However, the adequacy of these tools from a legal certainty and efficiency point of view can be criticised. In addition, the complexity of these measures and the uncertainty of the unitary patent regime will reduce their potential to act as safeguards. Thus, it must be acknowledged that the goal of legal certainty, as stated in the patent regime’s aim to promote innovation activities for start-ups and growth companies, has not been fully achieved.

Patenttioikeudenkäynnit Euroopassa: Onko start-up- ja kasvuyrityksillä keinoja puolustautua? Patenttijärjestelmän tulisi mahdollistaa oikeasuhtaisten oikeussuojakeinojen käyttö yrityksille niiden koosta riippumatta. Pienimpien start-up- ja kasvuyritysten kohdalla patentinloukkauskanteiden aiheuttamat merkittävät kustannukset voivat muodostua kasvun esteeksi. Väitteet patentin loukkauksesta voivat olla myös tarkoituksellisesti tehtyjä ja jopa ylimitoitettuja. Esimerkiksi patentinhaltija voi tarkoituksellisesti väittää, että patentin suojapiiri on laajempi kuin patenttihakemuksessa oli alkujaan tarkoitettu ja että start-up- tai kasvuyritys loukkaa tämän oikeutta. Tutkimuksen lähtöasetelmasta nousee esille kolme keskeistä näkökulmaa: start-up- ja kasvuyrityksillä on keskeinen rooli innovaatiotoiminnassa; eurooppalaisen patenttijärjestelmän on kyettävä vastaamaan patenttien ylikansalliseen täytäntöönpanoon ja yhtenäispatenttijärjestelmää koskeviin haasteisiin; sekä start-up- ja kasvuyrityksillä on oltava käytössään riittävät keinot puolustautua patentinlouk¬kauksia vastaan. Patentit ovat yrityksille taloudellinen väline. Niiden käyttö- ja hyödyntämistavat ovat laajentuneet ja monipuolistuneet. Myös patentteja koskevat teknologiansiirrot ovat lisääntyneet. Uusista tavoista ja keinoista hyödyntää patentteja taloudellisesti voidaan mainita patenttirahastot. Joidenkin patenttirahastojen pääasiallinen liiketoimintamalli on ostaa patentteja ja hankkia niiden avulla tuottoa vaatimalla lisenssimaksuja liiketoimintaa tuottavilta yrityksiltä, mahdollisesti jopa loukkauskanteita nostamalla. Väitöskirjassa etsitään vastausta kysymykseen: miten tehokkuutta ja oikeusvarmuutta voidaan patenttilainsäädännön turvin kasvattaa siten, että samalla tuetaan pienempiä yrityksiä. Tutkimuksessa asetetut normatiiviset tavoitteet rakentuvat oikeusvarmuuden ja tehokkuuden ympärille. Tutkimuksessa hyödynnetään oikeustaloustieteen metodeja ja oikeusvertailua. Uusi institutionaalinen oikeustaloustiede tutkii instituutioiden ja organisaatioiden välistä vuorovaikutusta. Instituutiot asetta¬vat toimintaympäristölle puitteet. Instituutioita ovat tässä tutkimuksessa säännöt ja oikeustapaukset, kun taas organisaatioita ovat puolestaan yritykset ja patenttirahastot. Oikeussuojakeinoista lähemmässä tarkastelussa ovat kustannusten jakautuminen, väliaikainen kielto oikeudenloukkauksen estämiseksi ja bifurkaatio (loukkaus- ja mitättömyyskanteiden jakaminen eri tuomioistuimeen). Tutkimuksessa tarkastellaan myös kanteiden yhdistämistä usean vastaajan tapauksessa. Edellä mainittujen keinojen lisäksi tutkimuksessa selvitetään oikeuden väärinkäytön kieltoa, määräävän markkina-aseman väärinkäytön kieltoa, IPR-täytäntöönpanodirektiiviä ja perusteettomia uhkauksia. Vertailussa keskitytään EU-lainsäädännön lisäksi patenttimarkkinoiden kannalta keskeisimpien eurooppalaisten maiden kansalliseen lainsäädäntöön. Tutkimuksessa on selvinnyt, että tarkastellut oikeussuojakeinot tarjoavat start-up- ja kasvuyrityksille keinoja puolustaa oikeuksiaan. Vaikka joidenkin oikeus¬suojakeinojen kohdalla oikeudellisen tulkinnan yhtenäisyys on saavutettu, keinojen riittävyyttä voidaan kuitenkin kritisoida erityisesti oikeusvarmuuden ja tehokkuuden näkökulmasta. Esimerkiksi keinojen monimutkaisuus ja yhtenäispatenttijärjestelmään liittyvät epävarmuudet tekevät oikeussuojakeinojen hyödyntämisestä haastavia pienimmille yrityksille. Voidaankin väittää, että oikeusvarmuuden tavoite, joka tutkimuksessa esitetyn mukaisesti heijastaa patenttijärjestelmän yleistavoitetta edistää innovaatioita, ei start-up- ja kasvuyritysten osalta täysin toteudu.